Examining Differences in Examinee Performance in Paper and Pencil and Computerized Testing - Puhan, Gautam; Boughton, Keith A; Kim, Sooyeon (The Journal of Technology, Learning and Assessment, 2007)
The study evaluated the comparability of two versions of a certification test: a paper-and-pencil test (PPT) and computer-based test (CBT). An effect size measure known as Cohen’s d and differential item functioning (DIF) analyses were used as measures of comparability at the test and item levels, respectively. Results indicated that the effect sizes were small (d < 0.20) and not statistically significant (p > 0.05), suggesting no substantial difference between the two test versions. Moreover, DIF analysis revealed that reading and mathematics items were comparable for both versions. However, three writing items were flagged for DIF. Substantive reviews failed to identify format differences that could explain the performance differences, so the causes of DIF could not be identified.